Vybrané problémy zaměstnávání osob se zdravotním postižením - Nádvorníková, Lenka (Univerzita Pardubice, 2011)
The paper deals with the issue of handicapped people, their status on the labor market and related legislation. First of all the author tries to point out to the terminological fragmentation in the definition of a handicapped person. Afterwards she examines the status on the labor market of such people and in conclusion briefly charakterize basics thesis of her reaserch, which is gong to be realized during this year.
Keywords: handicap; handicapped person; marginalization